(untitled) (Journal of actual problems of jurisprudence, 2019)
The article is devoted to the complex analysis of the civil offence low signi fi cance as an interdisciplinary category. The low signi fi - cance concept is researched as seen through the general law theory, criminal law and administrative law. The author has formulated the principle characteristics of this legal concept with the account for the general legal and interdisciplinary approaches to low signi fi cance. A conclusion is made that the offense low signi fi cance concept in the civil law has its own disciplinary features which should be legislatively fi xed.